Epigallocatechin gallate-rich fraction alleviates histamine-induced neurotoxicity in rats via inactivating caspase-3/JNK signaling pathways - Eman I. Hassanen; Hayam A. Mansour; Marwa Y. Issa; Marwa A. Ibrahim; Wafaa A. Mohamed; Mahmoud A. Mahmoud (Food and Chemical Toxicology, 2024)

Clinical and Molecular Profiles of a Cohort of Egyptian Patients with Collagen VI-Related Dystrophy - Wessam E. Sharaf-Eldin; Karima Rafat; Mahmoud Y. Issa; Hasnaa M. Elbendary; Noura R. Eissa; Bahaa Hawaary; Nagwa E. A. Gaboon; Reza Maroofian; Joseph G. Gleeson; Mona L. Essawi; Maha S. Zaki (Journal of Molecular Neuroscience, 2024)
Collagen VI-related dystrophies (COL6-RD) display a wide spectrum of disease severity and genetic variability ranging from mild Bethlem myopathy (BM) to severe Ullrich congenital muscular dystrophy (UCMD) and the intermediate severities in between with dual modes of inheritance, dominant and recessive. In the current study, next-generation sequencing demonstrated potential variants in the genes coding for the three alpha chains of collagen VI ( COL6A1 , COL6A2 , or COL6A3 ) in a cohort of Egyptian patients with progressive muscle weakness ( n = 23). Based on the age of disease onset and the patient clinical course, subjects were diagnosed as follows: 12 with UCMD, 8 with BM, and 3 with intermediate disease form. Fourteen pathogenic variants, including 5 novel alterations, were reported in the enrolled subjects. They included 3 missense, 3 frameshift, and 6 splicing variants in 4, 3, and 6 families, respectively. In addition, a nonsense variant in a single family and an inframe variant in 3 different families were also detected. Recessive and dominant modes of inheritance were recorded in 9 and 8 families, respectively. According to ACMG guidelines, variants were classified as pathogenic ( n = 7), likely pathogenic ( n = 4), or VUS ( n = 3) with significant pathogenic potential. To our knowledge, the study provided the first report of the clinical and genetic findings of a cohort of Egyptian patients with collagen VI deficiency. Inter- and intra-familial clinical variability was evident among the study cohort.

An atypical expression of core α-Dystroglycan and Laminin-α2 in skin fibroblasts of patients with congenital muscular dystrophies - Sahar Sabry; Mahmoud Y Issa; Mohamed S Abdel-Hamid; Noura R Eissa; Sherif F Abdel-Ghafar; Mona M Ibrahim; Maha S Zaki (Molecular Biology Reports, 2023)
Background Congenital muscular dystrophies (CMDs) result from genetically inherited defects in the biosynthesis and/or the posttranslational modification (glycosylation) of laminin-α2 and α-dystroglycan (α-DG), respectively. The interaction between both proteins is responsible for the stability and integrity of the muscle cell. We aimed to study the expression profiles of both proteins in two classes of CMDs. Subjects and methods Whole-exome sequencing (WES) was done for four patients with neuromuscular manifestations. The expression of core α-DG and laminin-α2 subunit in skin fibroblasts and MCF-7 cells was assessed by western blot. Results WES revealed two cases with nonsense mutations; c.2938G > T and c.4348 C > T, in LAMA2 encodes laminin-α2. It revealed also two cases with mutations in POMGNT1 encode protein O-mannose beta-1,2-N-acetylglucosaminyltransferase mutations. One patient had a missense mutation c.1325G > A, and the other had a synonymous variant c.636 C > T. Immunodetection of core α-DG in skin fibroblasts revealed the expression of truncated forms of core α-DG accompanied by reduced expression of laminin-α2 in POMGNT1-CMD patients and one patient with LAMA2-CMD. One patient with LAMA2-CMD had overexpression of laminin-α2 and expression of a low level of an abnormal form of increased molecular weight core α-DG. MCF-7 cells showed truncated forms of core α-CDG with an absent laminin-α2. Conclusion A correlation between the expression pattern/level of core α-DG and laminin-α2 could be found in patients with different types of CMD.

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies) - Nuria C. Bramswig; Aida M. Bertoli-Avella; Beate Albrecht; Aida I. Al Aqeel; Amal Alhashem; Nouriya Al-Sannaa; Maissa Bah; Katharina Bröhl; Christel Depienne; Nathalie Dorison; Diane Doummar; Nadja Ehmke; et al. (Human Genetics, 2018)

A novel frameshift mutation in the sterol 27-hydroxylase gene in an Egyptian family with cerebrotendinous xanthomatosis without cataract - Mohamed S. Abdel-Hamid; Mahmoud Y. Issa; Ghada A. Otaify; Maha S. Zaki (Metabolic Brain Disease, 2017)